Exploring soundscapes of Central Poland: a quantitative study of middle Pilica River basin within the Radomsko and Opoczno Hills - Adamiak, Maciej (Acta Geographica Lodziensia, 2024)
The research project focuses on analyzing the acoustic environment of the middle Pilica River basin. The study aims to understand the variability of soundscapes, the structure of biotic and abiotic sounds, and the impact of human-generated noise in various spatial and temporal contexts. As part of the research, sound recording devices were deployed in three test areas: the Czarna River, the Pilica River, and the Cieszanowice Reservoir, collecting over 2,200 hours of high-quality audio recordings. The collected data was analyzed using advanced sound processing and spatial analysis techniques. The results reveal a high acoustic diversity across the studied areas, considering both natural factors and anthropogenic influences. The findings contribute to a deeper understanding of the role of soundscapes in the Central Poland ecosystems, highlighting their importance for environmental conservation and spatial planning. The methodology developed within the project, combining geomatics, data engineering, and data analysis, enables research scalability and the exploration of new research areas.